Media Pembelajaran Bahasa Arab Bagi Anak Usia Dini di Era Digital Pasca Covid-19 - Akhmad Aufa Syukron; Taufiqul Rahman Syarif; Joko Susilo (Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah dan Ilmu Keguruan, UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to describe the Arabic language learning system for early childhood and find Arabic learning media for early childhood in the post-covid-19 digital era. The research method used is descriptive qualitative. The data used is based on library research, by reviewing and tracing various literature. The results of the study show that in learning Arabic for early childhood, the teacher must play an active role in keeping the child's mood in order to want to learn Arabic. Learning Arabic is an important thing to teach as a means of knowing Islam and its scientific treasures for Early Childhood Islamic Education, and several digital platforms have been found that can be used as media for learning Arabic for early childhood such as YouTube, applications/games, Arabic e-books and online sites for children aged 4-10 years.